Características hematológicas do tambaqui Colossoma macropomum Cuvier (Osteichthyes, Characidae) em sistema de monocultivo intensivo: II. Leucócitos - Tavares-Dias, Marcos [UNESP]; Sandrim, Elziane F. Silva; Campos-Filho, Eugênio de [UNESP] (Sociedade Brasileira de Zoologia, 1999)
The leukocytes parameters in approximately one-year-old freshwater fish Colossoma macropomum Cuvier, 1818 (tambaqui) kept in an intensive monobreeding system as well as the correlation among these parameters and the biometric data (total weight and standard length) were investigated. The mean value of the white blood cell count (WBC) in the peripheral blood of tambaqui was 2663.3±1288µl and in the differential count, the following means were observed: neutrophils (1566.2±754µl); lymphocytes (973.6±447µl); monocytes (86.7±123µl) and special granulocitic cells (7.8±144µl). The blood parameters studied were positively correlated among one another, but were negatively correlated with the standard length. However, no correlation was with the weigth of the animals was shown. The leukocytes in Colossoma macropomum kept in an intensive monobreeding system were morphologically similar to those of other Brazilian teleosts described in literature.
Hematological characteristics of tambaqui Colossoma macropomum Cuvier (Osteichthyes, Characidae) under intensive system: II. Leukocytes
Keywords: Characidae; Colossoma macropomum; freshwater fish; leukocytes; tambaqui